Formation of agricultural landscapes of saflor (Carthamus tinctorius) in the system of biologized crop - Nasiyev, B. N.; Yesenguzhina, A. N. (intellect, idea, innovation - 2021(Костанай), 2021)
Field experiments to study the biologized technology of safflower cultivationwere carried out in the spring and summer periods in the dry steppe zone of Western Kazakhstan. In the course of the research, traditional technology and technology with the use of biologic drugs and biofertilizers were studied. The area of the plots is 50 m 2, the repetition is three times, the location of the plots is random. The results of scientific research have shown that under the conditions of 2020, the highest oil collection of 2.29 c / ha was obtained with the combined use of the biological product Biodux, biofungicide Orgamica S and biofertilizers Organit N, Organit P (biologized technology) byseed treatment and treatment during the growing season. The use of traditional technology along with biological yield reduces theoil yield by 0.57 c / ha or by 33.13%. As a result of comparative studies of safflower oil content, an increase in oil content up to 30.0% was revealed when using biologized technology.
Keywords: рк; растениеводство; safflowe; biologized technology; growth and development; productivity; oil content; сафлор; биологизированная технология; рост и развитие; урожайность; отечественное издание; научный журнал; периодическое издание